Empowerment and Gender Dynamics in Wonder Woman: A Feminist Analysis - Karsum, Annabelle Mathilda; Tambunan, Aubrey Jemima; Jacobus, Benaiya Tristan; Tan, Emmanuel (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2025)
This study analyzes the 2017 film Wonder Woman through Judith Butler’s theory of gender performativity to explore how the narrative challenges patriarchal norms and redefines women’s roles in society. Using a feminist lens, the analysis highlights Diana’s experiences as she navigates contrasting gender expectations between Themyscira and patriarchal London. The study produces three key findings: 1) Diana’s resistance to restrictive social roles and clothing illustrates Butler’s view that gender is performed rather than innate; 2) her alienation within patriarchal London reflects the instability of gender identity when confronted with rigid societal norms; and 3) the solidarity between Diana and other women underscores Butler’s emphasis on collective resistance against oppressive structures. Ultimately, Wonder Woman emerges as a cultural text that embodies feminist ideals, inspiring new perspectives on empowerment, identity, and the reimagining of gender roles in modern society.